Police Abuse and Sex Workers - The Two Wings of the Butterfly : Negotiating Ethical Dilemmas in Participatory Action Research (PAR) in Bogotá, Colombia (2014)
Since September of 2012, we have been conducting Participatory Action Research (PAR) in the center of Bogotá with sex workers regarding their right to the public space known as 'La Mariposa' (The Butterfly), an open-air plaza where they often face discriminatory urban praxis and frequent abuse by police officers. While our PAR team has conducted research in 'The Butterfly' for over five years, the objectives, motivation and design of this PAR project were defined by community-based peer leaders and driven by their concerns and testimonies about the abuse and discrimination they have experienced from police in the plaza. Sex workers in the plaza have described these experiences in terms of unjustified detention, physical and verbal abuse, discrimination and abuse due to sexual orientation, and urban displacement. In this paper, we will discuss our PAR team's action research agenda and our collective work promoting sex worker's re-appropriation of their right to public space and the city